Moral Disengagement and Classroom Incivility against the Social Responsibility Character of Junior High School Students: Array - Susilawati Susilawati; Mungin Eddy Wibowo; Sunawan Sunawan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2020)
Nowadays social responsibility is significant to investigate. It is because in the academic world there are a number of students having low social responsibility. This behavior is realized by unfair actions in groups, bullying or intimidation practice. Concerning this phenomenon, the current study aimed at analyzing the prediction of students’ social responsibility from the perspective of moral disengagement and incivility. This correlational study involved 636 students with a portion of 49.5% of male students and 50.5% of female students. They were selected using cluster sampling from two junior high schools in Central Java. After that, these students were asked to fill in a moral disengagement scale, and classroom incivility scale. The results showed that moral disengagement and incivility significantly predicted social responsibility (R=0.336, R2=0.113, F=6.079, and P<0.01). Specifically, the findings of this study confirmed that the aspects of Moral Justification and Dehumanization, as well as intentional incivility, predict students’ social responsibility.